Adrenal insufficiency due to hemorrhage in a premature neonate:A case report - A.A Mohammand-Hoseini (Journal of Kerman University of Medical Sciences, 1997)
Neonatal adrenal hemorrhage is more common than previously suspected.in most cases the diagnosis is made by post-mortem autopsy.however massive hemorrhage is less common.the most important cause is  trauma during birth,other contributing factors are:macrosomia,diabetic mothers,breech presentation,congenital syphilis,anoxia,hemorrhagic disease, and prematurity.clinical manifestations of the disease varies with the degree and the extent of the hemorrhage.initial diagnosis is based on history,physical examination,sonographic studies,measurement of serum electrolytes,and is confrimed with hormonal studies.in this report a neonate is presentd,with disorders of electrolytes(low sodium,high potassium) and hypoglycemia,following recovery from an acute respiratory disease.the sonographyic results obtained from the upper posterior of the left kidney showed a hemorrhagic cyst.through hormonal examinations diagnosis of disorder of the adrenal gland was confirmed.